Islamic banking's challenges and goals - Mohd. Israil, Khaliq Ahmad (New Straits Times Press (NSTP), 2016)
“Perbankan Islam tiada ‘roh Islam, zalim” (Utusan, Oct 23, 2015) raises some serious concerns of society. This is despite the fact that “Islamic banking assets grew at an annual rate of 17.6 per cent between 2009 and 2013, and will grow by an average of 19.7 per cent a year in 2018 (The Economist, Sept 13, 2014); Khalid Howladar of Moody’s rating agency, calls this “a landmark year” for Islamic finance, in that it is moving from “a very esoteric asset class to one that’s more… global”. Islamic finance (IF) is developing at a remarkable pace. Indeed, Islamic banking, with the development of sukuk and the Islamic capital market, wealth management and Takaful, in Malaysia and elsewhere, is trying to offer alternative financing needs of society as opposed to the prevalent ribawi (interest) based system that is full of zulm (oppression and exploitation). However, Islamic banking is now being accused of operating in a similar fashion as its conventional counterpart, and being skewed to more profit and business-driven interests than serving the real needs of a just society...........